(untitled) (International Conference on Medical Science, Medicine and Public Health, 2025)
In medical science, the role of a laboratory assistant robot is very important and comprehensive. With the rapid development of technology in the field of modern medicine, laboratory assistant robots are of great help in medical diagnostic and research processes. These robots play an important role in reducing the human factor, improving outcome accuracy, speeding up the workflow, and ensuring safety.